2022
DOI: 10.1111/ijac.14231
|View full text |Cite
|
Sign up to set email alerts
|

Sintering kinetics and properties of NiFe2O4‐based ceramics inert anodes doped with TiN nanoparticles

Abstract: Sintering kinetics of NiFe 2 O 4 -based ceramics inert anodes for aluminum electrolysis doped 7 wt% TiN nanoparticles were conducted to investigate densification and grain growth behaviors. The linear shrinkage increased gradually with the increasing sintering temperature between 1000 and 1450 • C, whereas the linear shrinkage rate exhibited a broad peak. The maximum linear shrinkage rate was obtained at 1189.4 • C, and the highest densification rate was achieved at the relative density of 75.20%. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…51 Zhang and Xu also reported that addition of TiN to NiFe 2 O 4 could improve the electrical conductivity of the ceramic. 52 The maximum relative density and bending strength were achieved when TiN content was 7 wt% in the NiFe 2 O 4 -TiN composite. The electric conductivity of NiFe 2 O 4 -(7 wt%) TiN composite below 960 °C was 31.68 S cm −1 , which is nearly 10 times larger than that of undoped NiFe 2 O 4 material (3.36 S cm −1 ).…”
Section: Inert Anode Materialsmentioning
confidence: 90%
“…51 Zhang and Xu also reported that addition of TiN to NiFe 2 O 4 could improve the electrical conductivity of the ceramic. 52 The maximum relative density and bending strength were achieved when TiN content was 7 wt% in the NiFe 2 O 4 -TiN composite. The electric conductivity of NiFe 2 O 4 -(7 wt%) TiN composite below 960 °C was 31.68 S cm −1 , which is nearly 10 times larger than that of undoped NiFe 2 O 4 material (3.36 S cm −1 ).…”
Section: Inert Anode Materialsmentioning
confidence: 90%
“…[1][2][3] Significant progress has been made in the field of creating oxygen-evolving anodes and aluminum-wetted cathodes over the past two decades. [4][5][6][7][8][9] However, even the most corrosion-resistant materials cannot withstand the simultaneous effects of high temperature and aggressive electrolyte. The situation changes when the cryolite-alumina melt is replaced with a KF-AlF 3 -Al 2 O 3 based molten electrolyte offering an operating temperature in the range of 750 °C-850 °C.…”
mentioning
confidence: 99%
“…For the KF-AlF 3 -Al 2 O 3 based melts, the regularities of the cathode process on tungsten and glassy carbon, 24,25 as well as those of the anode process on glassy carbon, 26,27 and the anode behavior of various candidate materials of oxygen-evolving anodes (Cu, Ni, Cu-Al, Cu-Fe-Ni, Cu-Fe-Ni-Al, NiFe 2 O 4 et al) were studied earlier. [4][5][6][7][28][29][30] The interpretation of the mechanism and determination of anode process parameters according to the available results is challenging due to the superposition of chemical and electrochemical dissolution of the above oxygen-evolving anode materials, as well as the variability of the electrical resistance of the surface layer of the anode. To obtain new fundamental results for the purpose of their practical application, it is necessary to study the anode process on more stable materials (e.g., Pt, Au, Ir).…”
mentioning
confidence: 99%